2014
DOI: 10.5935/1806-0013.20140009
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia by non-specialists in pain

Abstract: BACKGROUND AND OBJECTIVES:Postoperative analgesia is often administered by the assistant physician non-specialist in pain management. This study aimed at evaluating the efficacy of immediate postoperative period analgesia with drugs prescribed by the assistant physician, non-specialist in pain. METHODS: This is a prospective, descriptive and observational study carried out by means of interviews with 186 patients operated in Hospital Santa Cruz. Postoperative pain was evaluated after 12 and 24 hours, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…As for analgesia, corroborating the present investigation, a study with the objective to evaluate the intensity of pain in 351 patients in the postoperative period showed that 98.9% of them received analgesia in the operating room (11) . Regarding postoperative analgesia, a study that included 186 patients also obtained similar results (17) . It may be noted that analgesia has been carried out according to WHO's recommendation, which advocate multimodal analgesia, with administration of various types of analgesic drugs (18) .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As for analgesia, corroborating the present investigation, a study with the objective to evaluate the intensity of pain in 351 patients in the postoperative period showed that 98.9% of them received analgesia in the operating room (11) . Regarding postoperative analgesia, a study that included 186 patients also obtained similar results (17) . It may be noted that analgesia has been carried out according to WHO's recommendation, which advocate multimodal analgesia, with administration of various types of analgesic drugs (18) .…”
Section: Discussionmentioning
confidence: 61%
“…As for the influence of pain on the Aldrete-Kroulik Scoring System, this study found a statistically significant relationship, showing that the lower the intensity of pain, the higher the system's scores. Despite pain not being covered by the AKSS, it is expected to result in possible physiological changes that may interfere with the system's scores (17) .…”
Section: Discussionmentioning
confidence: 99%
“…No aspecto segurança, verificou-se que os AINEs foram considerados seguros em 56,25% dos artigos selecionados, isoladamente ou em associação com os analgésicos opioides. Quando associados aos opioides, alguns efeitos adversos foram encontrados em maior proporção, como prurido, retenção urinária, náusea e, pelo menos um episódio de vômito [10][11][12][13][14][15] .…”
Section: Discussionunclassified
“… 9 10 Although the type of surgery may influence the pain site and intensity, both reviews included multiple surgery types such as abdominal, lumbar or dental surgery as well as laparoscopic surgery. 31 Moreover, the definition of acupuncture used in those studies is either too broad, including multiple types of acupuncture point stimulation such as acupressure and transcutaneous electrical acupoint stimulation, 9 or too narrow, only focusing on ear acupuncture. 10 Therefore, we will evaluate postoperative pain induced by laparoscopic surgery and define acupuncture treatment adequately as two components: (1) needling with penetration of the skin and (2) on specific points including traditional acupuncture points or painful points around the incision or shoulder region.…”
Section: Discussionmentioning
confidence: 99%